The power of images and the role of social media in Black Lives Matter’s social justice demands - Picarella, Lucia (SocietàMutamentoPolitica, 2023)
The proliferation of connections between the digital world and social activism shows that social media have become fundamental tools for collective action strategies. This article analyses the case study of Black Lives Matter, a movement that is expressing strong potential at a social and cultural level. The aim of this article is to observe the key role played by social media and images on the strengthening of identity, on the (re)signification of collective values, on the radicalisation of the action of the transversal demand for social justice. The previous study on the organisational and structural characteristics of the movement, and their intertwining with the maximisation of the possibilities offered by digital ecosystems, highlights in our conclusions the creation of a new social narrative that has modified perceptions and behaviour, and the strong pervasiveness of #BLM at a socio-cultural level opens up interesting possibilities in terms of pressure on the political-institutional system, political legitimisation and the creation of a structured dialogue between the establishment and civil society.